2017
DOI: 10.1002/smll.201702390
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic‐Functionalization of Silk Fibroin with Gold Nanoclusters Mediated by Keratin and Bioinspired Silk Synapse

Abstract: Silk fibroin (SF) offers great opportunities in manufacturing biocompatible/partially biodegradable devices with environmental benignity and biomedical applications. To obtain active SF devices of next generation, this work is to demonstrate a new functionalization strategy of the mesoscopic functionalization for soft materials. Unlike the atomic functionalization of solid materials, the meso-functionalization is to incorporate meso-dopants, i.e., functional molecules or nanomaterials, quantum dots, into the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 34 publications
2
75
1
Order By: Relevance
“…In other words, the HRS fitting results indicate that the charge‐transport behavior during the set process is in good agreement with the classical SCLC mode . In the LRS region of the orange frame, the fitted slopes are close to 1 (Figure S9c, Supporting Information), indicating ohmic conduction behavior and suggesting the formation of CFs during the set process . SCLC and the ohmic contact are responsible for the HRS and LRS, respectively, similar to other MDs operating by the Ag CFs RS mechanism …”
supporting
confidence: 71%
“…In other words, the HRS fitting results indicate that the charge‐transport behavior during the set process is in good agreement with the classical SCLC mode . In the LRS region of the orange frame, the fitted slopes are close to 1 (Figure S9c, Supporting Information), indicating ohmic conduction behavior and suggesting the formation of CFs during the set process . SCLC and the ohmic contact are responsible for the HRS and LRS, respectively, similar to other MDs operating by the Ag CFs RS mechanism …”
supporting
confidence: 71%
“…The difference is that the semiconducting or insulating switching layer does not contain movable metal ions or metal clusters; movable metal ions come from the redox reaction at the active electrode/switching layer interface upon electrical bias. The active electrode material is always Cu or Ag, and the switching layer can be Ta 2 O 5 , ZnO, HfO 2 , WO 3− x , ZnS, GeSe, SiGe, amorphous silicon, amorphous carbon, polymer, and silk fibroin . It has been found that lightly oxidized ZnS films present highly controllable memristive switching and synaptic performance, originating from a two‐layer structure of ZnS thin films, i.e., the lightly oxidized layer and unoxidized layer .…”
Section: Working Mechanisms Of Memristive Synapsesmentioning
confidence: 99%
“…Fitting results for the HRS (Figure S9c, Supporting Information) of the Ag/WS 2 /Pt device show that the charge transport behavior agrees well with the classical trap‐controlled space charge limited conduction, which is comprised of three sections. In the low‐voltage region from 0 to 0.6 V, the slope of 1.10 (close to 1) indicates the Ohmic region ( I ∝ V ); the voltage then increases from 0.6 to 1.7 V in the Child's law region ( I ∝ V 2 ) with the slope being 1.75; finally, there is a steep current increase region (1.7–3.4 V) with a slope of 3.28 . Furthermore, the I – V characteristics in the LRS of Ag/WS 2 /Pt are fitted as shown in Figure S9d (Supporting Information), where an Ohmic conduction behavior with a slope of ≈1 is apparent.…”
mentioning
confidence: 99%